Design and psychometrics for new measures of health-related quality of life in adults with type 1 diabetes: Type 1 Diabetes and Life (T1DAL). (April 2021) - Hilliard, Marisa E.; Marrero, David G.; Minard, Charles G.; Cao, Viena T.; de Wit, Maartje; DuBose, Stephanie N.; Verdejo, Alandra; Jaser, Sarah S.; Kruger, Davida; Monzavi, Roshanak; Shah, Viral N.; Wadwa, R. Paul; et al.
Abstract: Aims: To use a three-phase process to develop and validate new self-report measures of diabetes-specific health-related quality of life (HRQOL) for adults with type 1 diabetes. We report on four versions of the Type 1 Diabetes and Life (T1DAL) measure for people age 18–25, 26–45, 46–60, and over 60 years. Methods: We first conducted qualitative interviews to guide measure creation, then piloted the draft measures. We evaluated psychometric properties at six T1D Exchange Clinic Network sites via completion of T1DAL and validated measures of related constructs. Participants completed the T1DAL again in 4–6 weeks. We used psychometric data to reduce each measure to 23–27 items in length. Finally, we obtained participant feedback on the final measures. Results: The T1DAL-Adult measures demonstrated good internal consistency (α = 0.85–0.88) and test–retest reliability ( r = 0.77–0.87). Significant correlations with measures of general quality of life, generic and diabetes-specific HRQOL, diabetes burden, self-management, and glycemic control demonstrated validity. Factor analyses yielded 4–5 subscales per measure. Participants were satisfied with the final measures and reported they took 5–10 min to complete. Conclusions: The strong psychometric properties of the newly developed self-report T1DAL measures for adults with type 1 diabetes make them appropriate for use in clinical research and care.